Towards a runtime verification framework for the Ada Programming Language - Pedro, André Matos (2014)
Runtime verification is an emerging discipline that investigates methods and tools to enable the verification of program properties during the execution of the application. The goal is to complement static analysis approaches, in particular when static verification leads to the explosion of states. Non-functional properties, such as the ones present in real-time systems are an ideal target for this kind of verification methodology, as are usually out of the range of the power and expressiveness of classic static analyses. In this paper, we present a framework that allows real-time programs written in Ada to be augmented with runtime verification capabilities. Our framework provides the infrastructures which is needed to instrument the code with runtime monitors. These monitors are responsible for observing the system and reaching verdicts about whether its behavior is compliant with its non-functional properties. We also sketch a contract language to extend the one currently provided by Ada, with the long term goal of having an elegant way in which runtime monitors can be automatically synthesized and instrumented into the target systems. The usefulness of the proposed approach is demonstrated by showing its use for an application scenario.